Gelumpai Manuscript: Islamization and Development of Palembang Darussalam Sultanate (16th-17th century) - Hermanu Joebagio, Mayang Indah, Nur Fatah Abidin & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Gelumpai manuscript tells about the character of the Prophet Muhammad. Its positionin script tradition of huluan Palembang community is a representation of culturalsystem that indicates the acculturation feature between Java and local culture of huluanPalembang in the form of ulu or ka-ga-nga character. This study aims to analyse thecondition of Palembang community in the 16th-17th century based on Gelumpaimanuscript and to reflects the findings of the past into present. Research method used inthis investigation is literature study and critical discourse analysis approach in which itsunit of analysis is Gelumpai manuscript. This manuscript existed in PalembangDarussalam Sultanate in the 16th-17th century in which Islam was a foundation of thestate constitution. At that time, Muslim politicians proselytized Islam by usingGelumpai manuscript as a media containing the story of the Prophet Muhammadâscharacter that becomes ideal figure and can be implemented in Palembang communitylife.Keywords: Gelumpai manuscript, ka-ga-nga, Palembang Darussalam Sultanate